Why Are So Many Children Stunted in the Philippines? - Capanzana, Mario V.; Demombynes, Gabriel; Gubbins, Paul (World Bank, Washington, DC, 2020)
Nearly one in three children under age five in the Philippines is stunted, a key marker of undernutrition. This rate is high for the country's level of income. This paper provides the first detailed multivariate analysis of potential drivers of stunting in the Philippines, using data from the 2015 National Nutrition Survey. Potential drivers are analyzed individually and grouped in major categories. The analysis finds that stunting between 24-60 months is principally associated with suboptimal prenatal conditions and inadequate food security and diversity. If the results are given a causal interpretation, they imply that if all Filipino newborns had adequate prenatal conditions, the fraction stunted at age 24-60 months would fall by 20 percent. Similarly, providing adequate food security and diversity to all Filipino children would reduce stunting by 22 percent. Other factors -- including access to water, sanitation, and environmental conditions -- have less strong associations with stunting. The results point to a series of policy priorities to reduce stunting: supporting the nutrition and health of expectant mothers, ensuring access to contraception to reduce adolescent pregnancy, and ensuring that children consume a variety of healthy foods, including protein-dense foods such as milk, meat, and eggs.